Determinants for HIV testing and counselling in Nairobi urban informal settlements - Mgomella George; Oti Samuel; Kimani James K; Madise Nyovani J; Ziraba Abdhalah K; Matilu Mwau; Ezeh Alex (BMC, 2011)
Abstract Background Counselling and testing is important in HIV prevention and care. Majority of people in sub-Saharan Africa do not know their HIV status and are therefore unable to take steps to prevent infection or take up life prolonging anti-retroviral drugs in time if infected. This study aimed at exploring determinants of HIV testing and counselling in two Nairobi informal settlements. Methods Data are derived from a cross-sectional survey nested in an ongoing demographic surveillance system. A total of 3,162 individuals responded to the interview and out of these, 82% provided a blood sample which was tested using rapid test kits. The outcome of interest in this paper was HIV testing status in the past categorised as "never tested"; "client-initiated testing and counselling (CITC)" and provider-initiated testing and counselling (PITC). Multinomial logistic regression was used to identify determinants of HIV testing. Results Approximately 31% of all respondents had ever been tested for HIV through CITC, 22% through PITC and 42% had never been tested but indicated willingness to test. Overall, 62% of females and 38% of males had ever been tested for HIV. Males were less likely to have had CITC (OR = 0.47; p value < 0.001) and also less likely to have had PITC (OR = 0.16; p value < 0.001) compared to females. Individuals aged 20-24 years were more likely to have had either CITC or PITC compared to the other age groups. The divorced/separated/widowed were more likely (OR = 1.65; p value < 0.01) to have had CITC than their married counterparts, while the never married were less likely to have had either CITC or PITC. HIV positive individuals (OR = 1.60; p value < 0.01) and those who refused testing in the survey (OR = 1.39; p value < 0.05) were more likely to have had CITC compared to their HIV negative counterparts. Conclusion Although the proportion of individuals ever tested in the informal settlements is similar to the national average, it remains low compared to that of Nairobi province especially among men. Key determinants of HIV testing and counselling include; gender, age, education level, HIV status and marital status. These factors need to be considered in efforts aimed at increasing participation in HIV testing.